Extremely time-efficient Interval Endurance Training improves cardiometabolic Risk Profile and Inflammation Status for Obese Patient with increased risk of Metabolic Syndrome: A randomized-controlled Pilot Study - Reljic, Dejan; Frenk, Fabienne; Tobschall, Maike; Klaussner, Melanie; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

Maximum Heart Rate- and Lactate Threshold-Based Low-Volume High-Intensity Interval Training Prescriptions Provide Similar Health Benefits in Metabolic Syndrome Patients - Reljic, Dejan; Frenk, Fabienne; Herrmann, Hans Joachim; Neurath, Markus; Zopf, Yurdagül (Healthcare, 2023)
Exercise is an integral part of metabolic syndrome (MetS) treatment. Recently, low-volume high-intensity interval training (LOW-HIIT) has emerged as a time-efficient approach to improving cardiometabolic health. Intensity prescriptions for LOW-HIIT are typically based on maximum heart rate (HRmax) percentages. However, HRmax determination requires maximal effort during exercise testing, which may not always be feasible/safe for MetS patients. This trial compared the effects of a 12-week LOW-HIIT program based on: (a) HRmax (HIIT-HR), or (b) submaximal lactate threshold (HIIT-LT), on cardiometabolic health and quality of life (QoL) in MetS patients. Seventy-five patients were randomized to HIIT-HR (5 × 1 min at 80–95% HRmax), HIIT-LT (5 × 1 min at 95–105% LT) groups, both performed twice weekly on cycle ergometers, or a control group (CON). All patients received nutritional weight loss consultation. All groups reduced their body weight (HIIT-HR: −3.9 kg, p < 0.001; HTT-LT: −5.6 kg, p < 0.001; CON: −2.6 kg, p = 0.003). The HIIT-HR and HIIT-LT groups similarly, improved their maximal oxygen uptake (+3.6 and +3.7 mL/kg/min, p < 0.001), glycohemoglobin (−0.2%, p = 0.005, and −0.3%, p < 0.001), homeostasis model assessment index (−1.3 units, p = 0.005, and −1.0 units, p = 0.014), MetS z-score (−1.9 and −2.5 units, p < 0.001) and QoL (+10 points, p = 0.029, and +11 points, p = 0.002), while the CON did not experience changes in these variables. We conclude that HIIT-LT is a viable alternative to HIIT-HR for patients who are not able/willing to undergo maximal exercise testing.
CRIS-Team Scopus Importer:2023-03-23
Keywords: cardiometabolic health; cardiorespiratory fitness; exercise prescription; glycemic control; heart rate; interval training; lactate; maximal oxygen uptake; obesity; quality of life